Smart meter adoption: the role of consumer experience in using smart device. (March 2019) - Zamrudi, Zakky; Karim, Saiful; Faridha, Moethia; Maharani, Dewi; Dewi Kuraesin, Arlis
Abstract: To ensure sustainable development of energy efficiency, the use of smart device was considered to be a milestone in allowing household consumers to control their energy consumption record and a promising solution to deeply understand the consumer pattern of using power services provided by State power company (PLN). This study developed a model to measure the consumer preference in adopting the smart power in household sector. Data was collected by survey involving 437 samples in South East Kalimantan Province, Indonesia. The data was analysed by using SEM-PLS to assess the model evaluation. The findings of this study enhance the understanding of consumer perceptions and behaviour and are able to help the policy maker in considering the future policy in developing the power production and development plan. The results shows that most of variables are able to affect the intention to use smart power meter.